Enhancing the solvent resistance and thermomechanical properties of thermoplastic acrylic polymers and composites via reactive hybridisation. (August 2021) - Obande, Winifred; Gruszka, Weronika; Garden, Jennifer A.; Wurzer, Christian; Ó Brádaigh, Conchúr M.; Ray, Dipa
Graphical abstract: Highlights: Reactive acrylic/poly(phenylene ether) (PPE) blends were studied. Acrylic-PPE blends exhibited improved solvent resistance. Room-temperature vacuum processing of glass fibre-acrylic/PPE was demonstrated. Acrylic/PPE blends maintained full reshapability upon heating after polymerisation. Abstract: This work demonstrates the use of an engineering thermoplastic, poly(phenylene ether) (PPE) to enhance the solvent resistance and thermomechanical properties of liquid acrylic resin-based composites by a reactive hybridisation route. Oligomeric PPE with vinyl functionality was employed to attain chemical reactivity between the two constituents during the in-situ polymerisation process. Both unreinforced polymer blends and glass fibre-reinforced composites were studied; physical insights into the polymer structure and properties were obtained through complementary spectroscopic analysis, thermal analysis and microscopy. Spectroscopic analysis revealed the formation of multi-component mixtures in the blends, containing both CDCl3 -soluble and -insoluble constituents, with the latter likely corresponding to a reacted acrylic/PPE species. These findings show that incorporating reactive PPE into a reactive acrylic resin to produce a hybrid-matrix system is a simple, yet effective strategy towards enhancing solvent resistance (mass retention: 98% – PPE-modified; 72% – unmodified), while simultaneously enhancing the glass transition temperature (+9%) in acrylic-matrix composites.